Chemical vapor treatment of zinc oxide photoelectrodes for efficiency enhancement of dye-sensitized solar cells - Sasimonton Moungsrijun (2018)
© 2017, Springer-Verlag Wien. Abstract: ZnO photoelectrodes were successfully treated using hydrochloric vapor. The vapor was generated from hydrochloric acid solution with sonication assistance. The morphology showed a formation of plate-like structures after the vapor treatment, resulting in light scattering which was observed in terms of increased reflectance compared with the non-treated photoelectrodes. A dye-sensitized solar cell fabricated with the treated photoelectrodes exhibited an enhanced power conversion efficiency of 3.00% in comparison to the non-treated photoelectrodes base of 2.35%. The enhanced power conversion efficiency was observed in direct relation to the increased short-circuit current density. The increased short-circuit current density is due to the achieved light scattering in the photoelectrodes. Moreover, an extended open-circuit voltage was observed due to reduced electron recombination in the device. Therefore, a chemical vapor treatment of ZnO photoelectrodes via hydrochloric acid resulted in a successful scattering layer formation and a reduced recombination process for power conversion efficiency enhancement of ZnO dye-sensitized solar cells.